2015
DOI: 10.1186/s12929-015-0186-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dextromethorphan and oxycodone on treatment of neuropathic pain in mice

Abstract: BackgroundNeuropathic pain is a very troublesome and difficult pain to treat. Although opioids are the best analgesics for cancer and surgical pain in clinic, only oxycodone among opioids shows better efficacy to alleviate neuropathic pain. However, many side effects associated with the use of oxycodone render the continued use of it in neuropathic pain treatment undesirable. Hence, we explored whether dextromethorphan (DM, a known N-methyl-D-aspartate receptor antagonist with neuroprotective properties) could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 58 publications
3
30
0
Order By: Relevance
“…Besides, dextromethorphan could potentiate the effects of oxycodone. 7 However, little is known about the effect of oxycodone on the inflammatory response in microglia in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, dextromethorphan could potentiate the effects of oxycodone. 7 However, little is known about the effect of oxycodone on the inflammatory response in microglia in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that, pro‐inflammatory cytokines TNF‐α, IL‐1β, and IL‐6, all of which were important in the development and maintenance of neuropathic pain, were up‐regulated to initiate a neuroinflammatory cascade activated by CCI induction (Martucci et al ., ; Wang et al ., ; Yang et al ., ). The inflammatory protein iNOS produced large amounts of NO and participated in the pathophysiology of neuropathic pain (Levy et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“… 61 Oxycodone could suppress the glial activation and pro-inflammatory cytokines in mice models of neuropathic pain. 62 Most importantly, the inhibiting effect of oxycodone on glial activation takes place in the early stages of drug administration. 62 A recent study showed that medium and high concentrations of oxycodone could regulate the pro-inflammatory and anti-inflammatory molecules released by activated microglia in vitro.…”
Section: Discussionmentioning
confidence: 99%
“… 62 Most importantly, the inhibiting effect of oxycodone on glial activation takes place in the early stages of drug administration. 62 A recent study showed that medium and high concentrations of oxycodone could regulate the pro-inflammatory and anti-inflammatory molecules released by activated microglia in vitro. 63 We also examined the mRNA levels of GFAP and Iba1, which are astrocytic and microglial markers, respectively.…”
Section: Discussionmentioning
confidence: 99%